KARAKTERISTIK PRODUK BUBUK SARI JAGUNG MANIS INSTAN HASIL PENGERINGAN METODE SPOUTED-VORTEX-BED [Characteristics of Instant Sweet Corn Extract Powders Produced by Spouted-Vortex-Bed Drying Method] - Iwan Taruna; Neti Surami; . Sutarsi (Jurnal Teknologi dan Industri Pangan, 2013)
The characteristics of instant sweet corn extract powders produced by a spouted-vortex-bed (SVB) drying method was investigated as affected by the drying conditions. The sweet corn extract was prepared from shelled corn kernels of Bisi Sweet variety through washing, blanching, grinding, extracting and separating the soluble extract from the insoluble residue using a centrifugal filter. The extract was then dried at various drying conditions including inlet temperature (100-120°C), airflow rates (245-323 m3/h), feed rates (0.6-1.5 kg/h) and mass of Teflon pellets (0.7–1.3 kg). The dried products were sieved to obtain £ 60 mesh powders and analyzed for its moisture content, color attributes, density, solubility index, and water absorption capacity. The results showed that an increase in inlet temperatures and mass of Teflon pellets tended to decrease the moisture content of the powders. In most cases, the inlet temperatures influenced the L, a, b values of the sweet corn extract powders color. An increase in the inlet temperatures decreased the L and b values, but increased significantly the a value of the sweet corn extract powders. The effect of feed rates on the density of instant powders was identified only for drying temperatures between 100 and 120ºC. Increasing both airflow rates and inlet temperature at the mass of Teflon pellets of 1.3 kg decreased the solubility index of the sweet corn extract powders. Water absorption capacity of the sweet corn extract powders was influenced mainly by the airflow rate, feed rate and mass of inert particles.